IS ECONOMIC PERFORMANCE CONTRIBUTING TO ENVIRONMENTAL QUALITY? A CROSS-SECTIONAL ANALYSIS USING A GLOBAL DATASET - Ciprian Beniamin BENEA; Alexandru CONSTĂNGIOARĂ (Annals of the University of Oradea: Economic Science)
The European Green Deal strategy aims to decarbonize the EU economy and achieve ambitious sustainability goals. By evaluating and promoting environmentally sound development practices, the EU strives to lead by example and inspire global efforts towards a sustainable future. Moreover, The EU and OECD countries, alongside international frameworks, are committed to supporting vulnerable nations and advancing sustainable development worldwide. Through collaborative efforts and innovative policies, the EU and OECD aim to mitigate the impacts of climate change and pave the way for a more resilient and sustainable world.